2005
DOI: 10.1016/j.femsim.2005.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Determination of intracellular cytokines produced by Th1 and Th2 cells using flow cytometry in patients with brucellosis

Abstract: The aim of the study was to evaluate intracellular interferon-gamma (IFN-gamma), and interleukin-4 (IL-4) levels in pre- and post-treatment periods of brucellosis patients and to determine the relationship between these parameters and patients' clinical findings. Twenty-five patients diagnosed as brucellosis and 11 aged-matched healthy volunteers were included in the study. CD3+CD4+ T lymphocytes levels were significantly lower in patients with brucellosis as compared to the control group. CD3+CD8+ T lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 24 publications
0
21
1
Order By: Relevance
“…17,18 It has been reported that pretreatment CD3 + IFN-γ + levels were higher in responsive patients than the unresponsive group. 19 In addition to the studies showing induction of Th1-type immune response by brucellosis; Galanakis et al, 4 have reported that in children with brucellosis, serum IL-4 levels increased in the acute phase of the disease. In our study, IL-1 β and IL-4 levels were not statistically different between patient and control groups.…”
Section: Discussionmentioning
confidence: 98%
“…17,18 It has been reported that pretreatment CD3 + IFN-γ + levels were higher in responsive patients than the unresponsive group. 19 In addition to the studies showing induction of Th1-type immune response by brucellosis; Galanakis et al, 4 have reported that in children with brucellosis, serum IL-4 levels increased in the acute phase of the disease. In our study, IL-1 β and IL-4 levels were not statistically different between patient and control groups.…”
Section: Discussionmentioning
confidence: 98%
“…The response of the immune system to Brucella is complex and involves innate and adaptive immunity (2). The focus of our work was to investigate the pattern of circulating cytokines in brucellosis patients.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pattern of T-lymphocyte cytokine secretion is considered to be critical for the effectiveness of the protective anti-Brucella immune response (3, 7). It has been postulated that Th1 cytokines confer resistance, while Th2 cytokines facilitate the development of brucellosis (2,3,24,25,40,43,52). In animal models, gamma interferon (IFN-␥) induces macrophage activation and control of Brucella infection (16,18,43).…”
mentioning
confidence: 99%
“…Clonal T cell expansion is initiated with production of interleukin-2 (IL-2) and interleukin-12 (IL-12), which initiates a CD8+ cytotoxic response on Brucella -infected cells. Infected macrophages produce IL-12 and IFN-γ which regulate antigen presentation and may contribute to the limitation of intracellular bacterial replication through unknown mechanisms (Akbulut et al, 2005). Data also suggest that Brucella spp.…”
Section: T Cell Cytokine Responses To Brucella Infectionmentioning
confidence: 99%